Prenatal and early-life polychlorinated biphenyl (PCB) levels and behavior in Inuit preschoolers. - Verner, Marc-André; Plusquellec, Pierrich; Desjardins, Justine Laura; Cartier, Chloé; Haddad, Sami; Ayotte, Pierre; Dewailly, Éric; Muckle, Gina (Environment International, 2015)
International audience Background - Whereas it is well established that prenatal exposure to polychlorinated biphenyls (PCBs) can disrupt children's behavior, early postnatal exposure has received relatively little attention in environmental epidemiology. Objectives - To evaluate prenatal and postnatal exposures to PCB-153, a proxy of total PCB exposure, and their relation to inattention and activity in 5-year-old Inuits from the Cord Blood Monitoring Program. Methods - Prenatal exposure to PCBs was informed by cord plasma PCB-153 levels. We used a validated pharmacokinetic model to estimate monthly infants' levels across the first year of life. Inattention and activity were assessed by coding of video recordings of children undergoing fine motor testing. We used multivariable linear regression to evaluate the association between prenatal and postnatal PCB-153 levels and inattention (n=97) and activity (n=98) at 5years of age. Results - Cord plasma PCB-153 was not associated with inattention and activity. Each interquartile range (IQR) increase in estimated infant PCB-153 levels at 2months was associated with a 1.02% increase in the duration of inattention (95% CI: 0.04, 2.00). Statistical adjustment for the duration of breastfeeding slightly increased regression coefficients for postnatal level estimates, some of which became statistically significant for inattention (months: 2-4) and activity (months: 2-5). Conclusions - Our study adds to the growing evidence of postnatal windows of development during which children are more susceptible to neurotoxicants like PCBs.